Drexel dragonThe Math ForumDonate to the Math Forum



Search All of the Math Forum:

Views expressed in these public forums are not endorsed by Drexel University or The Math Forum.


Math Forum » Discussions » sci.math.* » sci.math

Topic: x + y + z >= xyz implies x^2 + y^2 + z^2 >= Axyz
Replies: 20   Last Post: Nov 1, 2013 4:48 AM

Advanced Search

Back to Topic List Back to Topic List Jump to Tree View Jump to Tree View   Messages: [ Previous | Next ]
quasi

Posts: 10,315
Registered: 7/15/05
Re: x + y + z >= xyz implies x^2 + y^2 + z^2 >= Axyz
Posted: Oct 30, 2013 5:50 AM
  Click to see the message monospaced in plain text Plain Text   Click to reply to this topic Reply

quasi wrote:
>
>Here's a nice challenge problem which I adapted from a past
>competition problem ...
>
>Problem:
>
>Find, with proof, the largest real number A such that
>
> x + y + z >= xyz
>
>implies
>
> x^2 + y^2 + z^2 >= Axyz
>
>My solution is elementary (avoids Calculus), but if a method
>based on Calculus yields an easy resolution, that would be worth
>seeing as well.


As a number of people have surmised, the maximum possible
value of A is sqrt(3).

Here's a proof ...

Let b = sqrt(3).

For x = y = z = b,

x^2 + y^2 + z^2 = b(xyz)

hence max(A) <= b.

To show that max(A) = b, it suffices to show that for
all real numbers x,y,z

x + y + z >= xyz

implies

x^2 + y^2 + z^2 >= bxyz

Suppose otherwise.

Thus, assume x,y,z are real numbers such that

x + y + z >= xyz

x^2 + y^2 + z^2 < bxyz

First

0 <= x^2 + y^2 + z^2

=> 0 < bxyz

=> xyz > 0

=> (x + y + z)^2 >= (xyz)^2

Next

(x-y)^2 + (y-z)^2 + (z-x)^2 >= 0

=> 2*(x^2 + y^2 + z^2) >= 2(xy + yz + zx)

=> 3(x^2 + y^2 + z^2) >= x^2 + y^2 + z^2 + 2(xy + yz + zx)

=> 3(x^2 + y^2 + z^2) >= (x + y + z)^2

=> 3(x^2 + y^2 + z^2) >= (xyz)^2

=> 3(bxyz) > (xyz)^2

=> xyz < 3b

But

x^2 + y^2 + z^2 >= 3(xyz)^(2/3) [by AM-GM]

=> bxyz > 3(xyz)^(2/3)

=> (bxyz)^3 > 27(xyz)^2

=> xyz > (27/b^3)

=> xyz > 3b

contradiction, which completes the proof.

quasi


Date Subject Author
10/25/13
Read x + y + z >= xyz implies x^2 + y^2 + z^2 >= Axyz
quasi
10/25/13
Read Re: x + y + z >= xyz implies x^2 + y^2 + z^2 >= Axyz
David C. Ullrich
10/25/13
Read Re: x + y + z >= xyz implies x^2 + y^2 + z^2 >= Axyz
quasi
10/26/13
Read Re: x + y + z >= xyz implies x^2 + y^2 + z^2 >= Axyz
Karl-Olav Nyberg
10/26/13
Read Re: x + y + z >= xyz implies x^2 + y^2 + z^2 >= Axyz
quasi
10/26/13
Read Re: x + y + z >= xyz implies x^2 + y^2 + z^2 >= Axyz
Peter Percival
10/25/13
Read Re: x + y + z >= xyz implies x^2 + y^2 + z^2 >= Axyz
David C. Ullrich
10/25/13
Read Re: x + y + z >= xyz implies x^2 + y^2 + z^2 >= Axyz
Don Coppersmith
10/25/13
Read Re: x + y + z >= xyz implies x^2 + y^2 + z^2 >= Axyz
Don Coppersmith
10/25/13
Read Re: x + y + z >= xyz implies x^2 + y^2 + z^2 >= Axyz
gnasher729
10/25/13
Read Re: x + y + z >= xyz implies x^2 + y^2 + z^2 >= Axyz
Peter Percival
10/27/13
Read Re: x + y + z >= xyz implies x^2 + y^2 + z^2 >= Axyz
gnasher729
10/27/13
Read Re: x + y + z >= xyz implies x^2 + y^2 + z^2 >= Axyz
dan.ms.chaos@gmail.com
10/27/13
Read Re: x + y + z >= xyz implies x^2 + y^2 + z^2 >= Axyz
Peter Percival
10/27/13
Read Re: x + y + z >= xyz implies x^2 + y^2 + z^2 >= Axyz
fom
10/30/13
Read Re: x + y + z >= xyz implies x^2 + y^2 + z^2 >= Axyz
quasi
10/30/13
Read Re: x + y + z >= xyz implies x^2 + y^2 + z^2 >= Axyz
Peter Percival
10/30/13
Read Re: x + y + z >= xyz implies x^2 + y^2 + z^2 >= Axyz
quasi
10/31/13
Read Re: x + y + z >= xyz implies x^2 + y^2 + z^2 >= Axyz
quasi
10/31/13
Read Re: x + y + z >= xyz implies x^2 + y^2 + z^2 >= Axyz
quasi
11/1/13
Read Re: x + y + z >= xyz implies x^2 + y^2 + z^2 >= Axyz
Phil Carmody

Point your RSS reader here for a feed of the latest messages in this topic.

[Privacy Policy] [Terms of Use]

© Drexel University 1994-2014. All Rights Reserved.
The Math Forum is a research and educational enterprise of the Drexel University School of Education.